1999
DOI: 10.3109/10826089909029387
|View full text |Cite
|
Sign up to set email alerts
|

Decisional Balance for Immoderate Drinking in College Students

Abstract: Immoderate drinking in college is common and is associated with significant negative sequelae. In this study, measures of Decisional Balance for Immoderate Drinking were developed. This construct is proposed to represent the basic decision-making process that is used by students when deciding whether to drink at immoderate levels or not. Furthermore this construct is embedded in a larger model of behavior change, the Transtheoretical Model of Change, which has been shown to be effective in understanding many h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 19 publications
2
43
2
Order By: Relevance
“…This cost-benefit analysis has been widely utilised in the past in the domains of psychology and psychiatry to assess motivations for various behaviours or cessation measures. These include investigating substance use and misuse (Carey et al, 1999;Migneault, 1999), smoking cessation (Velicer et al, 1985;Fava et al, 1995), exercise behaviour in adolescents (Nigg and Courneya, 1998) and readiness for change in anorexia nervosa (Cockell et al, 2002). To date, however, no known published empirical study exists which applies the DBS construct to ethical decisionmaking and the trade off between consumers various personal and social values.…”
Section: Decisional Balance Scalementioning
confidence: 96%
See 2 more Smart Citations
“…This cost-benefit analysis has been widely utilised in the past in the domains of psychology and psychiatry to assess motivations for various behaviours or cessation measures. These include investigating substance use and misuse (Carey et al, 1999;Migneault, 1999), smoking cessation (Velicer et al, 1985;Fava et al, 1995), exercise behaviour in adolescents (Nigg and Courneya, 1998) and readiness for change in anorexia nervosa (Cockell et al, 2002). To date, however, no known published empirical study exists which applies the DBS construct to ethical decisionmaking and the trade off between consumers various personal and social values.…”
Section: Decisional Balance Scalementioning
confidence: 96%
“…Past research has consistently found these eight categories balanced as two factors: positive gains and negative losses (Migneault et al, 1999). These are usually referred to, for brevity within the TTM literature, as ''pros'' and ''cons'' (e.g., Prochaska et al, 1992Prochaska et al, , 1993Rossi et al, 2001).…”
Section: Decisional Balance Scalementioning
confidence: 98%
See 1 more Smart Citation
“…The health behaviour, and related health promotion information seeking, considered in the present study is alcohol intake. There is considerable evidence that high levels of alcohol intake by university students can have negative consequences (Migneault, Velicer, Prochaska & Stevenson, 1999). In the present study, college students' information seeking of pro and anti drinking information is examined in light of their weekly alcohol unit intake, and their plans for behaviour change.…”
Section: Seeking Alcohol Information On the Internetmentioning
confidence: 99%
“…Items were taken from the Alcohol and Drug Consequences Questionnaire (Cunningham et al, 1997) and the Decisional Balance for Immoderate Drinking Scale (Migneault et al, 1999). All responses were on a 5-point Likert scale, anchored by not important and extremely important.…”
Section: Potential Mediators (A) Drinking To Cope With Stressmentioning
confidence: 99%